PERENCANAAN PENERAPAN MODUL KEGIATAN P5(KEWIRAUSAHAAN), PADA FASE B DI SDN BANJAREJO 2 TAHUN AJARAN 2022/2023 - Widiya Retno Wahyuni (Universitas PGRI Madiun, 2022)
The research conducted by the author aims to see the level of enthusiasm for the process of implementing the Modul P5 (Projek Penguatan Profil Pelajar Pancasila) as part of planning the implementation of the Kurikulum Merdeka, taking the theme of Entrepreneurship. The study involved 4th graders at SDN Banjarejo 2 in the 2022/2023 academic year. This study uses a type of qualitative method. By using exploratory studies, and using primary and secondary data sources. Primary data itself comes from the results of interviews, observations during implementation, and also study documentation. While the secondary data used is in the form of the curriculum, as well as the components that have been determined by the Kurikulum Merdeka, which the authors then form as the basic material for the Modul P5. The results showed a fairly high level of enthusiasm. project implementation is more scheduled and flexible and is not time to study general learning materials.